NEIGHBORHOODS AND DIGITAL DIVIDE: AN ANALYSIS OF A SMART CITY IN ARGENTINA - ALDERETE, María Verónica (Theoretical and Empirical Researches in Urban Management, 2025)
Few studies on the digital divide focus at the neighborhood level. The objective of this paper is to build the concept of smart neighborhoods based on the dimensions of a smart city: digital technology, mobility. governance and environment. The contribution is not only conceptual but also based on an exploratory-descriptive analysis of neighborhoods from Bahía Blanca, a smart city in Argentina. Results show that the lower availability of Internet and computers at home is associated with neighborhoods with Wi-Fi hotspots, registered neighborhoods and vulnerable. The greatest citizen participation is observed in unregistered neighborhoods. Most neighborhoods have public transportation and parks